ANALISIS MIDDLE INCOME TRAP DI INDONESIA - Asmirawati Asmirawati (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2017)
This paper aims to analyze middle income trap in Indonesia where per capita income is the main indicator in determining whether a country is included in the middle income category or not. By looking at the effect of high technology products , education level, direct investment and dependent ratio on per capita income in Indonesia. The results of this model use the ordinary least square method, which shows that the export of high-tech products has a positive and significant effect on per capita income, the level of education has a positive and significant effect on per capita income, direct investment has a negative and significant effect on per capita income, the ratio has a positive and significant effect. income per capita and high-tech product exports, level of education, direct investment, and the ratio have a significant effect on income per capita in Indonesia.